Engineering tissues with a zonal structure and composition mimicking native articular cartilage - Luo, Lu (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2015)
Engineering cartilage grafts with comparable functionality to the native tissue remains a major challenge in the field of regenerative medicine. The overall goal of this thesis was to engineer a cartilage graft with depth-dependent structure, composition and mechanical properties mimicking the native tissue. It has been previously shown that cartilage grafts mimicking certain aspects of the zonal composition of articular cartilage can be engineered by regulating the oxygen and mechanical environment through the depth of bone marrow derived mesenchymal stem cells (BM-IVISCs) seeded hydrogels (Thorpe et al., 2013). Such strategies were however limited by hypertrophy and the poor mechanical properties of the engineered grafts, motivating the use of infrapatellar fat pad derived mesenchymal stem cells (IFP-MSCs) for zonal cartilage tissue engineering.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin